Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1016/s0960-9822(03)00408-1
|View full text |Cite
|
Sign up to set email alerts
|

RNA Repair: Damage Control

Abstract: RNA in a cell is subject to many of the same insults as DNA. RNA damage can induce apoptosis and may be exploited for anti-cancer chemotherapy. It is a surprise, however, to learn that cells may repair RNA damage, suggesting a far greater significance of RNA in genotoxic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 17 publications
0
73
0
3
Order By: Relevance
“…If not repaired, damage to RNA molecules may lead to ribosomal dysfunctions and erroneous translation; thus, significantly affecting the overall protein synthesis mechanism (38,135). Moreover, RNA damage has been shown to cause cell cycle arrest and cell death with or without the contribution of p53 and inhibition of protein synthesis (11). Oxidative RNA modifications can occur not only in protein-coding RNAs, but also in noncoding RNAs that recently have been revealed to contribute to the complexity of the mammalian brain (109).…”
Section: Overview On Rna Oxidative Damages a Glimpse On Human Patholmentioning
confidence: 99%
See 1 more Smart Citation
“…If not repaired, damage to RNA molecules may lead to ribosomal dysfunctions and erroneous translation; thus, significantly affecting the overall protein synthesis mechanism (38,135). Moreover, RNA damage has been shown to cause cell cycle arrest and cell death with or without the contribution of p53 and inhibition of protein synthesis (11). Oxidative RNA modifications can occur not only in protein-coding RNAs, but also in noncoding RNAs that recently have been revealed to contribute to the complexity of the mammalian brain (109).…”
Section: Overview On Rna Oxidative Damages a Glimpse On Human Patholmentioning
confidence: 99%
“…An age-associated increase in oxidative nucleic acids damage, predominantly to RNA, has been recently highlighted in neurons from human and rodent brains; this phenomenon may play a fundamental role in the development of age-associated neurodegeneration (109). Oxidative damage to RNA molecules, both coding for proteins (mRNA) or performing translation (rRNA and tRNA), has been recently associated with the occurrence of neurodegenerative diseases, such as Alzheimer's disease (AD), Parkinson disease (PD), dementia with Lewy bodies, and amyotrophic lateral sclerosis (107) and its impact in cancer development cannot be excluded, at present (11). Remarkably, studies performed on either human samples or experimental models, show that RNA oxidation is a characteristic of aging neurons.…”
Section: Overview On Rna Oxidative Damages a Glimpse On Human Patholmentioning
confidence: 99%
“…It is noteworthy that studies on some anti-cancer agents have shown that RNA damage can lead to cell-cycle arrest and cell death, much as DNA damage does. RNA damage may cause cell death via involvement of a p53-dependent mechanism associated with inhibition of protein synthesis or a p53-independent mechanism different from inhibition of protein synthesis [155].…”
Section: Rna Oxidation and Repairmentioning
confidence: 99%
“…However, Aas et al [158] have suggested that the cells have at least one specific mechanism to repair RNA damage, indicating that cells may have a greater investment in the protection of RNA than previously suspected [138,155,159]. Indeed, alkylation damage in RNA is repaired by the enzyme AlkB in E. coli and the related protein in humans [158].…”
Section: Rna Oxidation and Repairmentioning
confidence: 99%
“…It is noteworthy that studies on some anti-cancer agents have shown that RNA damage can lead to cell-cycle arrest and cell death, much as DNA damage does. RNA damage may cause cell death via either pathway involving p53-dependent mechanism associated with inhibition of protein synthesis or p53-independent mechanism different from inhibition of protein synthesis [103].…”
Section: Rna Oxidation and The Biological Consequencementioning
confidence: 99%